PENGEMBANGAN MEDIA PRAKTIKUM MENGGUNAKAN HIDROPONIK RAKIT APUNG PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN - Puspita, Lia; Daningsih, Entin; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to assess how well static and dynamic floating raft hydroponic systems with different nutrient ratios support plant growth in laboratory practicals. The research follows a research and development (RnD) model with several modifications. In addition to the standard development stages, the study also integrates a media validation stage to ensure product quality. The research instruments include questionnaires, student responses, and laboratory worksheets. To measure the effectiveness of the floating raft hydroponic learning media, validation was conducted by media and material experts. The results of the prototype and media validation showed a feasibility level of 100%. The validation process involved a thorough examination of the media's functionality and effectiveness in a laboratory setting. Based on the assessment by media and material experts, the floating raft hydroponic prototype is deemed highly suitable for use as a learning media. This finding is reinforced by positive student responses, which reached a percentage of 90.97%. The high level of student approval indicates that the hydroponic systems not only meet educational standards but also engage students effectively, enhancing their learning experience in plant growth and hydroponics